The Effect of Applying the Window Shopping Learning Model on the Mathematics Learning Outcomes of Grade VIII Students at SMP Negeri 29 Sijunjung - Hesti Filmiari; Ramadoni Ramadoni; Dewi Yuliana Fitri (CV. Rayyan Dwi Bharata, 2023)
This research is motivated by the low results of students' mathematics learning. The purpose of this study was to determine the effect of applying the window shopping learning model to the learning outcomes of class VIII students at SMP Negeri 29 Sijunjung. This type of research is experimental research with a quantitative approach. The research design used was the Post-Test Only Control Group Design. The research population was all students of class VIII at SMP Negeri 29 Sijunjung. The technique used in sampling is simple random sampling. The research sample was class VIII 1 as the experimental class and class VIII 3 as the control class. The research instrument used in this study was in the form of a post-test in the form of a description. Furthermore, testing the hypothesis using the one-sided t test to be precise the right side. The results showed that the class using the window shopping learning model had an average of 64.79 and the class using the conventional learning model had an average of 51.04. The results of the hypothesis test obtained tcount = 2.10 and ttable = 2.00, then tcount ttable so that the hypothesis is accepted. Thus it can be concluded that there is an effect of applying the window shopping learning model to the learning outcomes of class VIII students at SMP Negeri 29 Sijunjung.